Vocalizing the Archipelago: Rhythmic Harmony and Textural Innovation in Contemporary Indonesian Choral Music - Kusumadewi , Kenya Permata (Indonesian Scientific Publication, 2024)
Contemporary Indonesian choral compositions increasingly incorporate traditional musical idioms such as gamelan and kecak into modern SATB frameworks. This study explores how selected choral works reinterpret these idioms by prioritizing rhythm, vocal texture, and articulation over conventional harmonic progressions. The objective is to understand how rhythm can function as a primary harmonic agent in a cappella settings. The methodology involves analytical comparison of three compositions Janger (Budi Susanto Yohanes), Cikala le Pong Pong, and Hela Rotan (both by Ken Steven). Through transcription, rhythm mapping, and texture classification, this study reveals the strategic layering of rhythmic motifs, percussive vocal effects, and responsorial structures across SATB and divisi settings. Results show that Janger employs interlocking vocal ostinati and contrasting articulations to emulate gamelan textures. Cikala le Pong Pong uses body percussion, chest voice, and glissandi to generate dissonant harmonic fields. Hela Rotan adapts Eastern Indonesian rhythmic idioms through responsorial phrasing, leading to emergent polyphonic verticalities. These techniques collectively redefine choral harmony through rhythmic density and vocal layering. Discussion highlights how these works negotiate cultural fidelity and artistic innovation. They challenge Western centric harmonic paradigms by elevating rhythm and texture as compositional pillars. Such approaches not only contribute to decolonizing harmonic theory but also enrich global choral repertoires through culturally grounded, structurally inventive music.